F4(w-5)-4=-3(-7w+4)-7w

Simple and best practice solution for F4(w-5)-4=-3(-7w+4)-7w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F4(w-5)-4=-3(-7w+4)-7w equation:



4(F-5)-4=-3(-7F+4)-7F
We move all terms to the left:
4(F-5)-4-(-3(-7F+4)-7F)=0
We multiply parentheses
4F-(-3(-7F+4)-7F)-20-4=0
We calculate terms in parentheses: -(-3(-7F+4)-7F), so:
-3(-7F+4)-7F
We add all the numbers together, and all the variables
-7F-3(-7F+4)
We multiply parentheses
-7F+21F-12
We add all the numbers together, and all the variables
14F-12
Back to the equation:
-(14F-12)
We add all the numbers together, and all the variables
4F-(14F-12)-24=0
We get rid of parentheses
4F-14F+12-24=0
We add all the numbers together, and all the variables
-10F-12=0
We move all terms containing F to the left, all other terms to the right
-10F=12
F=12/-10
F=-1+1/5

You can always share this solution

See similar equations:

| 11x-5=8x-6 | | -4w+10=-2(w-7) | | 3/10=10x | | 4(w-4)-8w=-8 | | 4(5+8d)D=84 | | 2-6(1-x)+x=4(2x-1)-x | | 17x-3=-43 | | 80-2x=30x= | | (10x+6)(6x+4)=90 | | (a+2)*(a+3)=3 | | -6=(5x-12)/3 | | 2a+1=10 | | (2x-1)(x+17)=0 | | 1+7p+p=1 | | 3(m+5)=12 | | 10(z+1)-5(z-2)=2(z-2)+2(z-1) | | (4a-1)=-23- | | 2(m-1)=-5(4m-m) | | -6w-14=8(w-7) | | 3(2x-3)-3=3(x-2)+9 | | X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) |

Equations solver categories